2021
DOI: 10.1152/japplphysiol.00657.2020
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent compression induces transitory hypoxic stimuli, upstream vasodilation and enhanced perfusion of skin capillaries, independent of age and diabetes

Abstract: The benefit of enhanced shear stress to the vascular endothelium has been well documented in conduit arteries but is less well understood in skin microcirculation. The study aim was to provide physiological evidence of the vascular changes in skin microcirculation induced by intermittent pneumatic compression (IPC) of 1 second cuff inflation (130 mmHg) every 20 seconds to the palm of the hand for 30 minutes. The oxygenation and hemodynamics of dorsal mid-phalangeal finger skin microcirculation were assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…This increases blood flow and vascular function, due to active vasodilatation and hyperemic reactions. The results are consistent with the results of Thorn et al [17] that insisted on the positive effect of hand intermittent pneumatic compression evoking transitory hypoxic stimuli in distal finger skin microcirculation inducing vasodilation of arterial inflow vessels, in young and older subjects and older subjects with type 2 diabetes mellitus. Winberg et al [18] confirmed our findings that intermittent pneumatic compression may be a plausible treatment modality for improving self-reported foot sensation as well as static and dynamic balance control, raising NCV as a sign of improvement.…”
Section: Discussionsupporting
confidence: 92%
“…This increases blood flow and vascular function, due to active vasodilatation and hyperemic reactions. The results are consistent with the results of Thorn et al [17] that insisted on the positive effect of hand intermittent pneumatic compression evoking transitory hypoxic stimuli in distal finger skin microcirculation inducing vasodilation of arterial inflow vessels, in young and older subjects and older subjects with type 2 diabetes mellitus. Winberg et al [18] confirmed our findings that intermittent pneumatic compression may be a plausible treatment modality for improving self-reported foot sensation as well as static and dynamic balance control, raising NCV as a sign of improvement.…”
Section: Discussionsupporting
confidence: 92%
“…In 2012, Palazzin et al reported that MLD of lower limbs led to a reduction in blood and urinary glucose in patients affected by type 1 diabetes mellitus [ 37 ]. Recently, in 2021, Thorn et al [ 38 ] demonstrated that IPC of an upper limb induced arterial inflow vessels vasodilation with enhanced perfusion and determined the maximum capillary recruitment in subjects suffering from T2DM. Moreover, Nikolovska et al showed that this tool speeds up lymphatic drainage and disposal of metabolic products [ 39 ].…”
Section: Introductionmentioning
confidence: 99%